Comparison the Quality of Template DNA isolated by Column Method with and without Centrifugation: Perbandingan Kualitas DNA Template yang diisolasi dengan Metode Kolom dengan dan tanpa Sentrifugasi - Wardana, Aji Cakra; Mushlih, Miftahul (Indonesian Journal of Innovation Studies, 2021)
DNA isolation is the first step in molecular biology work. The quality of the DNA template is very important because it can affect the DNA amplification reaction. The application of centrifugation to the sample is expected to produce a Buffy coat layer containing nuclear cells. This study aims to compare the quality of the DNA template isolated from the column with and without centrifugation. This research used descriptive experimental method. The samples used were 16 samples with the division of 8 samples given centrifugation treatment and 8 samples without centrifugation. DNA isolation column method is a DNA isolation method that uses a silica membrane, where the silica membrane works as a filter for DNA that is split from the cell. The DNA isolation method column was carried out according to the standard protocol on the Geneaid DNA mini Kit Blood/Tissue. The concentration and purity of DNA were measured using UV-Vis Spectrophotometry at 260 nm and 280 nm. Visualization of DNA isolation results was carried out using 1% agarose gel. The results of measuring the quality of DNA samples using the column method with centrifugation showed better results with clearer visualization of DNA bands than samples without centrifugation. The results of the T dependent statistical test on both samples of p value < 0.05 showed that there was a significant difference in DNA quality with centrifuged and non-centrifuged treatment.